BIBLIOMETRIC STUDY ON ELECTROCHEMICAL RESEARCH BASED ON PAPERS PUBLISHED IN CORE JOURNALS - Meyyappan, N.; Srinivasan, R.; Shanmugasigamani, K. (Malaysian Journal of Library and Information Science, 1997)
Describes a bibliometric study on electrochemistry based on publication counts in core electrochemical journals. The journals covered are Journal of the Electrochemical Society (USA), Journal of Electrochemistry (Switzerland), Electrochimica Acta (UK), Journal of Applied Electrochemistry (UK) and Journal of Power Sources (Swit-zerland). The CD-ROM editions 1991 and 1992 of Chemistry Citation Index (CCI) were analysed. A total of 4,020 published items (articles, notes, letters, etc) were retrieved. The top productive countries in the field of chemistry are identified and the standing of these countries in the field of electrochemistry are compared. All countries that have contributed at least one item in any of these core journals are listed along with the number of papers published and the ranks they hold.; international co-authorship matrix among the top productive countries is provided; individual institutions all over the world which contribute significantly during this period are listed; the authorship pattern, types of published items, and distribution range of cited references and related records are studied.